ANALISIS DETERMINAN PARTISIPASI KERJA PENDUDUK LANJUT USIA DI KOTA DENPASAR - Intan Tarisa Puspita, Ni Made Rai; Murjana Yasa, I Gusti Wayan; Ayuningsasi, Anak Agung Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.03.TAHUN.2024, 2024)
The elderly population in Indonesia continues to grow every year, and the percentage of the elderly in Indonesia has approximately doubled. The phenomenon shows that there are still many elderly people who are actively involved economically to produce goods or services, either as a form of self-actualization or because of economic pressure. The purpose of this study was to analyze the effect of education level, health, number of dependents, and non-work income simultaneously and partially on the work participation of the elderly population in Denpasar City. This research was conducted in Denpasar City. The sampling technique used is purposive sampling with a sample size of 120 elderly people. The data analysis technique used is multiple linear regression analysis. The results of the analysis show that the level of education, health, number of dependents, and non-work income simultaneously affect the work participation of the elderly population in Denpasar City. The level of education, health, and the number of dependents have a positive and significant effect on the work participation of the elderly population in Denpasar City. Non-employment income has no significant effect on the work participation of the elderly population in Denpasar City.